The first small fluorescent probe as Tyrosyl-DNA phosphodiesterase 1 (TDP1) substrate. (October 2019) - Tang, Zhan-Yong; Zhang, Yu; Chen, Yu-Ting; Yu, Qian; An, Lin-Kun
Abstract: Tyrosyl-DNA phosphodiesterase 1 (TDP1) is a recently discovered enzyme specifically repairing DNA topoisomerase IB-mediated DNA damage, and is a rational anticancer target. Herein, we report the design and synthesis of the first small fluorescent probe 1 as TDP1 substrate. Probe 1 is a specific substrate of TDP1 and shows good spectroscopic properties with more than 140-fold fluorescence enhancement. A novel TDP1 inhibition assay was established using 1 as substrate. The possible cleavage pathway of 1 by TDP1 was also studied. Highlights: The first small fluorescent probe 1 as TDP1 substrate was synthesized. Probe 1 is a specific substrate of TDP1. Probe 1 shows more than 140-fold fluorescence enhancement. A novel screening assay for TDP1 inhibitors was established.